2018
DOI: 10.1177/1352458517737393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of puberty on multiple sclerosis risk and course

Abstract: Puberty occurs over several years and is a time of major sex hormone changes. These changes impact many physiological functions including immune system maturation. This review details the current understanding of the impact of puberty on the risk to develop multiple sclerosis (MS) and the age at which it occurs, as well as its effect on the risk of relapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In paediatric MS, the prepubertal onset is extremely rare with a sex ratio of 1:1 6. However, after puberty, the incidence rises dramatically with a female preponderance, suggesting that key immune changes occur during or after puberty under the influence of sex hormones 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In paediatric MS, the prepubertal onset is extremely rare with a sex ratio of 1:1 6. However, after puberty, the incidence rises dramatically with a female preponderance, suggesting that key immune changes occur during or after puberty under the influence of sex hormones 5…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that, after puberty, the incidence and prevalence of MS are significantly higher in women compared with men 5. In addition, female patients also experience a more active disease (higher relapse rate and higher number of active lesions at MRI), suggesting that sex-specific differences in the immune-pathophysiology of the disease may contribute to a more prominent inflammatory disease in female patients with MS already from adolescence 5–9…”
Section: Introductionmentioning
confidence: 99%
“…Menarche represents the end of puberty and is regulated by genetic and several environmental factors (BMI, diet, and exercise). 15,16 It has been hypothesized that early menarche or earlier sexual maturation will involve more prolonged exposure to sexual hormones, which might be related to an increased risk of MS. A Canadian study reported an increased risk of MS in women with a younger age at menarche—menarche in controls occurred at 12.6 years compared to 12.4 years in patients with MS ( p = 0.00017)—but did not find any association between age at menarche and age at MS onset. 9 Our study did not include controls and cannot address this specific question; however, we did not find a relationship between age at puberty and age at MS onset or long-term clinical course of the disease (risk of second attack, McDonald MS, risk of disability) even after controlling for age at CIS, topography, OB, MRI, treatment, and body size self-perception at menarche.…”
Section: Discussionmentioning
confidence: 99%
“…For each variant, effect estimates on both childhood and adult obesity measures are included in a weighted multivariable regression model. 16 In addition, given the proposed role for pubertal timing in MS and its correlation with body weight status, 34,35 we repeated the analysis with age at puberty as a third exposure (along with childhood and adult obesity measures) using genetic determinants of age at menarche as previously reported (n=329,245). 35,36 The genetic architecture of pubertal timing across both sexes is highly correlated (rg=0.75; p=1.2x10 -79 ), allowing these variants to provide insight into pubertal timing in males as well.…”
Section: Multivariable Mendelian Randomizationmentioning
confidence: 99%